2016
DOI: 10.1186/s12885-016-2148-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the distance between the primary tumor and brainstem in the patients with locally advanced nasopharyngeal carcinoma

Abstract: BackgroundBrainstem dose limitations influence radiation dose reaching to tumor in the patients with locally-advanced nasopharyngeal cancer (NPC).MethodsA retrospective analysis of the prognostic value of the distance between the primary tumor and brainstem (Dbs) in 358 patients with locally-advanced NPC after intensity-modulated radiation therapy (IMRT). Receiver operating characteristic (ROC) curves were used to identify the cut-off value to analyze the impact of Dbs on tumor dose coverage and prognosis.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…In this study, CR rate was significantly higher in the PET/CT-guided DP-IMRT group than in patients administered CT-based IMRT (99.0% vs 92.9%, P  = 0.037), suggesting that the risk for local residual tumor was significantly decreased by dose escalation using the DP-IMRT technique. Our findings using a PET/CT-guided DP-IMRT regimen demonstrated that LFFS, DMFS and OS compared favorably to other reports using CT-based IMRT and chemotherapy for NPC patients [14, 28, 29]. Liu et al [28] reported that 185 patients with stage III to IVb NPC were treated by CT-based IMRT and chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, CR rate was significantly higher in the PET/CT-guided DP-IMRT group than in patients administered CT-based IMRT (99.0% vs 92.9%, P  = 0.037), suggesting that the risk for local residual tumor was significantly decreased by dose escalation using the DP-IMRT technique. Our findings using a PET/CT-guided DP-IMRT regimen demonstrated that LFFS, DMFS and OS compared favorably to other reports using CT-based IMRT and chemotherapy for NPC patients [14, 28, 29]. Liu et al [28] reported that 185 patients with stage III to IVb NPC were treated by CT-based IMRT and chemotherapy.…”
Section: Discussionsupporting
confidence: 77%
“…The measured HI values of 0.16 for GTV-P and 0.15 for PTV-G in our study were not inferior to the HI values of 0.09, 0.19, and 0.30 for each PTV reported by Mao et al,19 indicating the good homogeneity of this method. With a median follow-up time of 50 months, a satisfactory 3-year LFFS rate of 91.9% was achieved, which was similar to historical outcome rates ranging between 82.1% and 91.1% 2022. Therefore, this method of reduced target delineation after IC was feasible to some extent, but further study is required to confirm these findings.…”
Section: Discussionsupporting
confidence: 64%
“…Although the SEER database contains a large number of records, it lacks other important information. For instance, data about the concrete position and growth pattern of tumor were not accessible in SEER database, which were important for tumor categorization and evaluating the prognosis of patients with LGBSG (20,21,29). Moreover, other clinical features of patients including functional status and neurologic symptoms were not available, which were reported to be predictive factors of patient prognosis (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%